The Effect of Live Yeast and Yeast Extracts Included in Lactation Diets on Sow and Litter Performance - Jenna A. Chance; Jordan T. Gebhardt; Joel M DeRouchey; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joseph A. Loughmiller; Brian Hotze (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 80 sows (Line 241; DNA Genetics) across three farrowing groups were used in a study to evaluate the effect of feeding live yeast and yeast extracts to lactating sows on sow and litter performance. Sows were blocked by BW and parity on d 110 of gestation and allotted to 1 of 2 dietary treatments. Dietary treatments consisted of a standard corn-soybean meal lactation diet or a diet that contained yeast-based preand probiotics (0.10% Actisaf Sc 47 HR+ and 0.025% SafMannan; Phileo by Lesaffre, Milwaukee, WI). Diets were fed from d 110 of gestation until weaning (approximately d 19). A tendency (P= 0.073) was observed for increased feed intake from farrowing to weaning when sows were fed a diet with yeast additives compared to the control diet. There was no evidence (P>0.10) that sow treatment influenced any other sow or litter performance criteria. In conclusion, feeding live yeast and yeast extracts tended to increase feed intake during lactation but did not influence other sow or litter performance measurements.
Keywords: lactation; sow; yeast; yeast extract